Targeted overexpression of tumor necrosis factor-α increases cyclin-dependent kinase 5 activity and TRPV1-dependent Ca2+ influx in trigeminal neurons. Issue 6 (June 2016) - Rozas, Pablo; Lazcano, Pablo; Piña, Ricardo; Cho, Andrew; Terse, Anita; Pertusa, Maria; Madrid, Rodolfo; Gonzalez-Billault, Christian; Kulkarni, Ashok B.; Utreras, Elias
Abstract : Abstract: We reported earlier that TNF-α, a proinflammatory cytokine implicated in many inflammatory disorders causing orofacial pain, increases the activity of Cdk5, a key kinase involved in brain development and function and recently found to be involved in pain signaling. To investigate a potential mechanism underlying inflammatory pain in trigeminal ganglia (TGs), we engineered a transgenic mouse model (TNF glo ) that can conditionally overexpresses TNF-α upon genomic recombination by Cre recombinase. TNF glo mice were bred with Nav1.8-Cre mouse line that expresses the Cre recombinase in sensory neurons to obtain TNF-α:Nav1.8-Cre (TNF-α cTg) mice. Although TNF-α cTg mice appeared normal without any gross phenotype, they displayed a significant increase in TNF-α levels after activation of NFκB signaling in the TG. IL-6 and MCP-1 levels were also increased along with intense immunostaining for Iba1 and GFAP in TG, indicating the presence of infiltrating macrophages and the activation of satellite glial cells. TNF-α cTg mice displayed increased trigeminal Cdk5 activity, and this increase was associated with elevated levels of phospho-T407-TRPV1 and capsaicin-evocated Ca 2+ influx in cultured trigeminal neurons. Remarkably, this effect was prevented by roscovitine, an inhibitor of Cdk5, which suggests that TNF-α overexpression induced sensitization of the TRPV1 channel. Furthermore, TNF-α cTg mice displayed more aversive behavior to noxious thermal stimulation (45°C) of the face in an operant pain assessment device as compared with control mice. In summary, TNF-α overexpression in the sensory neurons of TNF-α cTg mice results in inflammatory sensitization and increased Cdk5 activity; therefore, this mouse model would be valuable for investigating the mechanism of TNF-α involved in orofacial pain. Abstract : TNF-α produced sensitization of TRPV1 through increase of Cdk5 activity in mouse trigeminal ganglion neurons, implicating its potential role in orofacial pain induced by neuroinflammation.